Optimizing the Speed and Explosive Power Performance of Football Players: The Effect of a Six-Week Neuromuscular Training - Singh, Laishram Santosh; Singh, Ningthoujam Rojesh; Singh, W. James; Singh, Okram Robinson; Mola, Dessalegn Wase (Physical Education Theory and Methodology, 2024)
Background. Football players require high levels of speed and explosive power to perform effectively on the field, making these physical attributes critical for success. Neuromuscular training has been proposed as a method to enhance these performance metrics. Objectives. The purpose of the present study was to examine the effect of neuromuscular training on the speed and explosive power performance of football players. Materials and methods. A total of thirty male football players (aged 20 to 26 years) from Imphal West District, Imphal, Manipur, India, who had participated in national-level competitions, were selected for the study. The subjects were randomly assigned into two equal groups: an experimental group (n = 15) and a control group (n = 15). Both groups were assessed before the intervention for speed and explosive power performance using the 50 m dash speed test and the standing broad jump test to determine the baseline significance of the selected variables. Following the initial assessments, the experimental group underwent a supervised neuromuscular training program, while the control groupreceived no special training. The neuromuscular training was conducted over a period of six weeks, with sessions held five days a week (Monday to Friday), each lasting 60 minutes. Results. The experimental group confirmed significant improvements in both speed and explosive power compared to the control group (p < 0.05). The mean and standard deviation of speed for the experimental group were 7.15 ± 0.71 in the pre-test and 6.54 ± 0.61 in the post-test. For explosive power, the values were 2.36 ± 0.32 in the pre-test and 2.55 ± 0.39 in the post-test. The notable enhancements in speed and explosive power performance in the experimental group are likely attributed to the six-week neuromuscular training program, which facilitated rapid physical adaptation among the football players. Conclusions. Implementing the six-week neuromuscular training program effectively enhanced the speed and explosive power performance of football players. This type of training has been demonstrated to be highly effective for optimizing these performance metrics in football players.